Exploration of the Optimum Rice Husk Biochar for Atrazine and 2,4-D Removal: Different Pyrolysis and Modification Conditions - BINH, Quach An; ANH, Nguyen Hong; KIEU, Vo Thi Diem; DANG, Nguyen Hai; HAO, Nguyen Quy; TUNG, Tra Van (GeoScience Engineering, 2020)
In this study, the best RHB (rice husk biochar) was investigated through the effect of pyrolysis synthesis processes and modifications. Five biochars were synthesized from rice husk waste materials at different pyrolysis temperatures (400 to 600 °C) in oxygen-limited conditions. The biochars were modified by acids to remove minerals on the surface area. The characteristics of the biochars were determined including surface morphology, specific surface area, and functional groups. The herbicide adsorption was accomplished by the batch equilibration method. The result indicated that the biochar that synthesized 500 °C for 6 h had the highest maximum adsorption capacity. The optimum RHB was biochar modified with HF acid. The optimum biochar had less or no minerals and it achieved abundant functional groups on the surface areas. The pore volume distributions in pore sizes of micropores and narrow mesopores played an important role to perform the uptake of the herbicides, they were in the range of 7.90 % and 59.26 %, respectively. The high-efficiency removals of atrazine and 2,4-D by optimum biochar were 82.70 % and 95.10 %, respectively. The rice husk biochar is a suitable adsorbent to remove herbicides from the aqueous environment. Keywords: Adsorbent; Adsorption; Atrazine; Biochar; 2,4-D. DOI 10.35180/gse-2020-0042